Research Collaboration System in Indian Science as Evident from Scientific Database - Garvita Jhamb, Meera, K.P Singh (Journal of Information & Systems Management, 2018)
In this research we find how the Indian geoscience researchers collaborate and produce science output. The dataset for this analysis the papers indexed in the global database, called as the Web of Science which is used. The dataset is extracted with scientific records for the period of 20 years i.e. 1998-2017. We produce a few indicators which are given as belo. The values of degree of collaboration is 0.90, the collaboration coefficient is 0.62, and collaborative index is 3.8 which indicates that the output is emerged as the result of scientific collaboration and research network. We found that the output of the total research, 55.4% came from national level of collaboration which is followed by the international level at 34.3%. The most prefered nation for collaboration seems to be USA with 56 papers followed by UK with 25 papers in a total of 200 internationally collaborated papers. Interestingly we observed that the internationally collaborated papers get more citations (59.6%) whereas the natonal contribution is 34.8%. Citation per paper (CPP) for internationally collaborated articles is 22 while that for domestic collaborations is 8. Overall CPP is 13. Finally we found that the maximum 81.3% of papers are contained in the top ten journals of which Himalayan Geology occupies the top position. Among them the Journal Geology received highest citation per paper which stands at CPP=39.